Amplificadores de instrumentação integrados de baixo consumo e baixo ruído para aplicações portáteis voltadas ao tratamento de biosinais - Viana, Nayana Letícia de Morais (2019)
This work presents some proposals for low-power and low-noise instrumentation amplifiers aimed at biopotential conditioning, using 0.5 µm CMOS technology. Firstly a theoretical framework about the treatment of biopotentials for wearable and/or portable applications is presented. Following is done a state of the art review for low power and low noise instrumentation amplifier architectures. A study about the types of pseudoresistors presented in the literature is also performed. Once this is done, the methodology used to perform this work is presented. Two OTA (Transconductance Operational Amplifier) architectures were selected to compare noise and consumption, namely: FoldedCascode and Current-Mirror. Current-Mirror topology showed better behavior related to consumption and gain, while Folded-Cascode behaved better related to the noise. It is also proposed a methodology for comparative analysis of pseudo resistors, in order to choose one that optimally meets the requirements of high resistance and low variability. Three instrumentation amplifiers have been implemented: two one-stage amplifiers (single-ended and fully-differential), and one with two-stages, in order to meet gain and frequency requirements for the entire range of the biopotentials. The results shown that the three configurations meet the specifications for use in low power and low noise acquisition systems for portable biosignal applications.